Forging ties: the effect of discrimination on Asian Americans' perceptions of political commonality with Latinos. (26th May 2020) - Lu, Fan
ABSTRACT: There is little consensus on how discrimination against racial minorities affects their potential for forming political alliances with out-groups who are also targets of racial discrimination. Furthermore, the relationship between Latinos and Asian Americans is an under-explored area in the study of inter-minority relations. Using data from the 2008 National Asian American Survey (NAAS), I test the argument that individual and group-based discrimination against Asian Americans increase their perceptions of political commonality with Latino Americans. There is only partial support for this argument. The relationship between discrimination and perceptions of political commonality varies by the context in which discrimination occurs and the Asian ethnic group in question.